Special education services and teaching of English: experiences of inclusive education in a school in Augusto Corrêa-PA. - FARO, Rodrigo da Costa (2024)
At the beginning of each school year, teachers encounter more and more students with special learning needs. Often, teachers are not able to receive this audience because they have not had continuing education in special and inclusive education. The purpose of this paper is to report on the teaching methods and practices used with a student with multiple disabilities, who studies in a public school in the municipality of Augusto Corrêa-Pará, focusing on the teacher of the specialized educational care room and the teacher of the regular English language classroom. The methodology of this research consisted of semi-structured interviews with the participants in order to report on the teaching practices used by this student's teachers in his educational process, starting from the care in the ESA room to his inclusion in the regular class. This work proposes reflections based on national legislation on inclusive education for people with disabilities.